Measurement of inclusive jet production and nuclear modifications in pPb collisions at root s(NN)=5.02 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Ero, J.; Flechl, M.; Friedl, M.; et al. (My University, 2016)
Inclusive jet production in pPb collisions at a nucleon-nucleon (NN) center-of-mass energy of root s(NN) = 5.02 TeV is studied with the CMS detector at the LHC. A data sample corresponding to an integrated luminosity of 30.1 nb(-1) is analyzed. The jet transverse momentum spectra are studied in seven pseudorapidity intervals covering the range -2.0 < eta(CM) < 1.5 in the NN center-of-mass frame. The jet production yields at forward and backward pseudorapidity are compared and no significant asymmetry about eta(CM) = 0 is observed in the measured kinematic range. The measurements in the pPb system are compared to reference jet spectra obtained by extrapolation from previous measurements in pp collisions at root s = 7 TeV. In all pseudorapidity ranges, nuclear modifications in inclusive jet production are found to be small, as predicted by next-to-leading order perturbative QCD calculations that incorporate nuclear effects in the parton distribution functions.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Collaboration, C. M. S. (2016). Measurement of inclusive jet production and nuclear modifications in pPb collisions at root s(NN)=5.02 TeV. European Physical Journal C, 76(7), 25. doi:10.1140/epjc/s10052-016-4205-7
Keywords: Quark-Gluon Plasmas; P-Pb Collisions; Root(Nn)-N-S=5.02 Tev; Atlas; Detector; Centrality